1979
DOI: 10.1128/aem.38.3.461-465.1979
|View full text |Cite
|
Sign up to set email alerts
|

Respiration and viability of thermally injured Saccharomyces cerevisiae

Abstract: Resting cells of Saccharomyces cerevisiae Y25 were heated at 560C for 0 to 2 min. Respiratory activity of the cells reflected the severity of the heat stress. The endogenous respiration was approximately 50 IlI of 02/mg per h for cells heated for 2 min at 560C as compared with 2 ,ul of 02/mg per h for nonheated cells. There was a distinct decrease in respiration after 1 to 3 h, and after 20 h the respiration rate of heated cells was less than that of nonheated cells. Along with increased rates of endogenous re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1982
1982
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 13 publications
(4 reference statements)
1
1
0
Order By: Relevance
“…Experimental design did not permit conclusions to be drawn concerning the mechanism of action of antioxidants on injured and healthy cells. However, increased endogenous respiratory activity of heat-injured S. cerevisiae cells, indicating a requirement for increased energy during repair, has been reported by Graumlich and Stevenson (11). In their study, glucose was shown to increase the total oxygen uptake of heat-stressed cells in comparison with unheated cells, and this increased oxygen consumption may have reflected utilization of added glucose to meet increased energy demands of damaged cells.…”
Section: 0f-supporting
confidence: 62%
“…Experimental design did not permit conclusions to be drawn concerning the mechanism of action of antioxidants on injured and healthy cells. However, increased endogenous respiratory activity of heat-injured S. cerevisiae cells, indicating a requirement for increased energy during repair, has been reported by Graumlich and Stevenson (11). In their study, glucose was shown to increase the total oxygen uptake of heat-stressed cells in comparison with unheated cells, and this increased oxygen consumption may have reflected utilization of added glucose to meet increased energy demands of damaged cells.…”
Section: 0f-supporting
confidence: 62%
“…The maximum relative volume is then reached at 60°C and retained until the end of the baking process. The initial expansion can be explained by the CO 2 production of yeast cells till the death of yeast cells sets in at ~ 50°C [ 35 37 ]. During this initial baking phase, an expansion rate of 0.104 min -1 was determined by a linear model (relative volume–baking time), which is markedly higher compared to the gas production rate during the fermentation phase.…”
Section: Resultsmentioning
confidence: 99%